Bioprinting and Tissue Engineering: Recent Advances and Future Perspectives. Issue 9 (7th October 2013) - Seliktar, Dror; Dikovsky, Daniel; Napadensky, Eduardo
Abstract Bioprinting in tissue engineering applies 3D printing technologies towards the development of precisely designed scaffolds for tissue repair and organ replacement. The printed scaffolds may incorporate polymeric constituents together with biological payloads, including cells and biochemically active additives. The scaffolds can be designed with spatial precision, achieving both biochemical and biophysical heterogeneity that mimic the extracellular environment of the body's tissues. Recent advances in 3D bioprinting have applied a strategy of controlling physical properties together with bioactivity to influence specific interactions with cellular systems, including spatial and temporal patterns of biochemical and biomechanical cues that regulate cell behavior and improve tissue integration. Important new advances in tissue engineering have now been realized based on these approaches, and clinical applications for printed scaffolds continue to drive further improvements to 3D bioprinter technologies.